Photorhabdus antumapuensis sp. nov., a novel symbiotic bacterial species associated with Heterorhabditis atacamensis entomopathogenic nematodes - Castaneda-Alvarez, Carlos; Machado, Ricardo A R; Morales-Montero, Patricia; Boss, Anja; Muller, Arthur; Prodan, Simona; Zamorano, Alan; San-Blas, Ernesto; Půža, Vladimír; Aballay, Erwin (International journal of systematic and evolutionary microbiology, 2022)
One motile, Gram-negative, non-spore-forming and rod-shaped symbiotic bacterium, strain UCH-936T, was isolated from Heterorhabditis atacamensis nematodes. Results of biochemical, physiological, molecular and genomic analyses suggest that it represents a new species, which we propose to name Photorhabdus antumapuensis sp. nov. Digital DNA-DNA hybridization shows that strain UCH-936T is more closely related to Photorhabdus kleinii DSM 23513T, but shares solely 50.5 % similarity, which is below the 70% cut-off value that delimits species boundaries in bacteria. Phylogenetic reconstructions using whole-genome sequences show that strain UCH-936T forms a unique clade, suggesting its novel and distinct taxonomic status again. Similarly, comparative genomic analyses shows that the virulence factor flagella-related gene fleR, the type IV pili-related gene pilL and the vibriobactin-related gene vibE are present in the genome of strain UCH-936T but absent in the genomes of its closest relatives. Biochemically and physiologically, UCH-936T differs also from all closely related Photorhabdus species. Therefore, Photorhabdus antumapuensis sp. nov. is proposed as a new species with the type strain UCH-936T (CCCT 21.06T=CCM 9188T=CCOS 1991T).
Keywords: taxonomy; DNA bakterií; Virulence Factors; Phylogeny; Sequence Analysis, DNA; zastoupení bazí; Nematoda; RNA ribozomální 16S; Heterorhabditis; zvířata; Base Composition; RNA, Ribosomal, 16S; faktory virulence; entomopathogenic bacteria; sekvenční analýza DNA; hlístice; Rhabditoidea; DNA, Bacterial; mastné kyseliny; fylogeneze; symbiotic bacteria; Photorhabdus; Bacterial Typing Techniques; Animals; techniky typizace bakterií; Fatty Acids